IRE1-bZIP60 Pathway Is Required for Nicotiana attenuata Resistance to Fungal Pathogen Alternaria alternata - Xu, Zhen; Song, Na; Ma, Lan; Wu, Jinsong (Frontiers in Plant Science, 2019)
As an endoplasmic reticulum (ER) stress sensor, inositol-requiring enzyme 1 (IRE1) splices the bZIP60 mRNA, and produces an active bZIP60 transcription factor that regulates genes involved in the unfolded protein response (UPR) during ER stresses. This IRE1-bZIP60 pathway is conserved in plant species and recently implicated in plant-pathogen interaction. However, it is unclear whether this IRE1-bZIP60 pathway is involved in Nicotiana attenuata resistance to necrotic fungal pathogen, Alternaria alternata. In this study, transcriptional levels of chaperone protein genes, including luminal binding protein (BiP), protein disulfide isomerase (PDI), Calnexin 1-like (CNX 1-like) and calreticulin (CRT), and genes involved in IRE1-bZIP60 pathway, were all significantly induced in N. attenuata leaves after A. alternata inoculation. Silencing IRE1 or bZIP60 lead to N. attenuata plants more susceptible to A. alternata, which were associated with reduced gene expressions of Feruloyl-CoA 6’-hydroxylase 1 (F6’H1), a gene encoding a key enzyme for phytoalexin scopoletin and scopolin biosynthesis. Further electro-mobility shift assays (EMSA) indicated that bZIP60 protein of spliced form could directly bind to the promoter region of F6’H1 in vitro. JA signaling pathway is required for N. attenuata resistance to A. alternata. Interestingly, the fungus-elicited transcriptional levels of BiP, PDI, CNX 1-like, CRT, IRE1 and bZIP60(s) were all significantly decreased in JA-deficient or JA-insensitive plants. Meanwhile, those genes were significantly induced by methyl jasmonate (MeJA) when applied exogenously. However, the transcriptional levels of JA-regulated genes allene oxide synthase (AOS) and lipoxygenease 3 (LOX3) were not affected in plants impaired with IRE1-bZIP60 pathway. Thus, it is concluded that IRE1-bZIP60 pathway is required for N. attenuata resistance to A. alternata, and JA signaling pathway plays an important role in the elicitation of chaperone protein genes and IRE1-bZIP60 pathway.